Large‐Amplitude Mountain Waves in the Mesosphere Observed on 21 June 2014 During DEEPWAVE: 2. Nonlinear Dynamics, Wave Breaking, and Instabilities. Issue 17 (18th September 2019) - Fritts, David C.; Wang, Ling; Taylor, Michael J.; Pautet, Pierre‐Dominique; Criddle, Neal R.; Kaifler, Bernd; Eckermann, Stephen D.; Liley, Ben
Abstract: Weak cross‐mountain flow over the New Zealand South Island on 21 June 2014 during the Deep Propagating Gravity Wave Experiment (DEEPWAVE) led to large‐amplitude mountain waves in the mesosphere and lower thermosphere. The mesosphere and lower thermosphere responses were observed by ground‐based instruments in the lee of the Southern Alps supporting DEEPWAVE, including an Advanced Mesosphere Temperature Mapper, a Rayleigh lidar, an All‐Sky Imager, and a Fabry‐Perot Interferometer. The character of the mountain wave responses at horizontal scales of 30–90 km reveals strong "sawtooth" variations in the temperature field suggesting large vertical and horizontal displacements leading to mountain wave overturning. The observations also reveal multiple examples of apparent instability structures within the mountain wave field that arose accompanying large amplitudes and exhibited various forms, scales, and evolutions. This paper employs detailed data analyses and results of numerical modeling of gravity wave instability dynamics to interpret these mountain wave dynamics, their instability forms, scales, and expected environmental influences. Results demonstrate apparently general instability pathways for breaking of large‐amplitude gravity waves in environments without and with mean shear. A close link is also found between large‐amplitude gravity waves and the dominant instability scales that may yield additional abilities to quantify gravity wave characteristics and effects. Key Points: Weak mountain waves at low altitudes can achieve breaking amplitudes in the mesosphere under suitable propagation conditions Mountain wave breaking occurs via 3‐D instability dynamics predicted by high‐resolution modeling in various environments Mountain wave instability dynamics evolve on short time scales and impose significant intermittency in wave amplitudes and momentum fluxes